La comunicación asertiva y su incidencia en el aprendizaje de los estudiantes del primero de Bachillerato General Unificado - Lozada Márquez, Ana del Rosario (2020)
Assertive communication as a mediating tool in the resolution of conflicts in the teaching-learning process has important sociological and psychological implications that demand a better professional preparation of the teacher. However, in Baccalaureate there are still high prevalence difficulties in using assertive communication in pedagogical practice, generating difficulties in the mediation of conflicts between peers and teachers, which has an impact on student learning. Observing hostility, school rejection until dropping out, therefore, is that this research aims. To determine the incidence of assertive communication between teacher / student and its influence on the learning of the first of the Unified General Baccalaureate, of the Catalina Cadena Miranda Educational Unit. Methodology………